EDUKASI MASYARAKAT MOTIVASI USAHA BAGI IBU RUMAH TANGGA DI YAYASAN ALKAHFI DESA SUKOREJO KABUPATEN BOJONEGORO - Edy Suhartono; Hening Anitasari; Defryan Agung Adhyaksa; Aditya Baskara Wahyu Dewata (Jurnal Abdi Masyarakat, 2025)
This community service activity aims to provide assistance to housewives in understanding and developing business potential. This activity is carried out by providing training that includes delivering business motivation materials, interactive discussions, business planning simulations, and evaluations. Participants are given insight into the importance of economic independence, how to manage small capital, and marketing strategies that are relevant to local conditions. The results of the analysis showed an increase in participants' understanding and motivation in starting a business. Most people showed a high interest in implementing the business ideas presented during the training. In this activity, an interactive discussion session was provided to help participants identify business opportunities that are in accordance with their potential and resources. With this program, it is hoped that the community can increase their understanding of entrepreneurship, grow their motivation to become entrepreneurs, apply knowledge in real life, and have a positive economic impact through new businesses that are pioneered, so that they can make a real contribution to family economic independence and active participation of housewives in supporting local economic development.